Dust Exposures, IgE Levels, History of Allergy, and Symptoms of Allergy in Poultry Workers - Wijayanti, Yuni; Sutomo, Adi Heru; Astuti, Indwiani; Asmara, Widya (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
Poultry dust exposure may increase workers’ health risks, particularly in the form of respiratory allergic reactions. This study aimed to identify mold content of the dust and to analyze the association between dust exposure, IgE level, history of allergy, and symptoms of allergy. This study used cross sectional design with total samples of 33 workers. The data were analyzed using chi-square test and multivariate logistic regression. This study found 93.33% growth of Aspergillus sp., 69.7% work duration > 3 years, 84.8% high IgE levels, 18.2% history of allergy, and 69.7% symptoms of allergy. Dust exposure and history of allergy did not show significant correlation with symptoms of allergy while IgE levels had significant correlation with p-value of 0.036. Workers with high IgE-level were 15.986 times more likely to have symptoms of allergy (p-value 0.028). Aspergillus sp. as dust allergen potentially increased IgE levels and might become the base for facilitation of early and independent preventive and promotive efforts of workers’ health.